The potential influence of injuries in basketball over the basketball players - Bartosz Borowski; Małgorzata` Kozioł; Agnieszka Markiewicz-Gospodarek (Kazimierz Wielki University, 2022)
Background: From all the sports around the world, basketball is certainly such popular that it attracts people who loves to watch it, as well as people who loves to play it. Due to the form of this sport, it is very likely to get an injury while playing it. Aim of the study: The aim of this study was to determine the most repeated types of injuries that might occur to the basketball players, how many basketball players get injured during their professional career, what the convalescence after the injury looked like, and how the COVID-19 pandemic influenced the group of professional basketball players of the EBL (Energa Basket Liga), 1LM and 2LM. Material and methods: Data collected from a survey sent to 19 basketball players in February 2021. Results: Most of the basketball players who took part in the examination at some point during their career suffered from an injury, at least one. The part of the body that was affected the most was the lower limb. As the players stated, the injuries that they had were the reason of a long absence in the game. For most of the time the convalescence process consisted of co-operation with the physiotherapist. The mental health of the players was disparately affected by the ensuing injury. As well the COVID-19 pandemic influenced the interviewees' contracts, and most of the times, their mental health's condition. Among the players who were tested positive with the SARS-CoV-2 virus, each one developed some kind of signs of the infection. Conclusion: Each of the examined players during their professional career at least once suffered form an injury that influenced their physical health, and sometimes also mental health condition. In general, the pandemic period affected badly not only in a sphere of mental health, but also social life elements, such as ability to work out and prepare to the season.